Efficacy and safety of transcutaneous auricular vagus nerve stimulation plus pregabalin for radiotherapy-related neuropathic pain in patients with head and neck cancer (RELAX): a phase 2 randomised trialResearch in context - Xuzheng Zuo; Yongteng Xu; Shaojian Li; Jingru Jiang; Jinyuan Wang; Yingying Zhu; Dong Pan; Honghong Li; Yanting Chen; Yanmin Chen; Xiaoming Rong; Dong Zheng; et al. (EClinicalMedicine, 2025)
Summary: Background: Rapid relief of radiotherapy-related neuropathic pain (RRNP) in head and neck cancer (HNC) survivors is challenging when relying solely on pharmacologic treatments, especially in the early stages of medication. Whether transcutaneous auricular vagus nerve stimulation (taVNS) can effectively and rapidly control the RRNP in HNC survivors remains uncertain. Methods: The RELAX trial was a randomised, parallel, sham-controlled trial conducted at four centres in China. We randomly assigned (1:1) HNC survivors with moderate-to-severe RRNP (as defined by Numeric Rating Scale [NRS] score of ≥4) to receive taVNS or sham stimulation (concha of the left ear) for 30 min twice daily over 7 days. Participants, outcome assessors, and statisticians were blinded to assignment and intervention. All patients also received a basal dose of pregabalin (75 mg twice daily). The primary outcome was pain intensity reduction, as measured by the change of NRS scores from baseline to day 7. This trial is registered at ClinicalTrials.gov, NCT05543239. Findings: Between September 16, 2022, and December 1, 2023, 116 eligible patients (mean age, 50.8 [standard deviation (SD), 8.8] years; 40 [34.5%] were women) were randomly assigned into groups. All patients completed NRS score at baseline and day 7, and 112 (96.6%) completed 80% or more of the intervention course. The pain intensity at baseline was 5.79 (SD, 1.59) in the taVNS group and 5.66 (SD, 1.54) in the control group. At day 7, pain intensity decreased by 2.43 (SD, 2.19) in the taVNS group and 1.12 (SD, 1.64) in the Control group; between-group difference, 1.31 points (95% confidence interval [CI], 0.60–2.02; P = 0.00042). The most common adverse event (AE) related to taVNS was mild, transient local skin irritations at the electrode site (8.6% versus 1.7%, P = 0.21), and no serious AE were associated with the device. Interpretation: In this trial, taVNS for 7 days at the initial stage of pregabalin treatment resulted in significantly better pain relief in HNC survivors with moderate-to-severe RRNP with no serious AE. Further prospective investigations to observe the longer term effects of taVNS on RRNP are warranted. Funding: This study was supported by Ministry of Science and Technology of the People's Republic of China, National Natural Science Foundation of China, Department of Science and Technology of Guangdong Province and Guangzhou Science and Technology Bureau.